Design and fabrication hand operated can crusher / Muhammad Ammar Che Suffian - Che Suffian, Muhammad Ammar (2023)
The study of manufacturing was very important to carry this project to ensure that student understand on what are needs to do. This project is about designing and fabrication the Can Crusher to helps people easy to crush the Aluminum, tins, and soda cans. This project involves the process of designing the crusher using considering forces and ergonomic factor for people to use. After the design has complete, it was transformed to its real product where the design is used for guideline. This project also requires ensuring the safety for indeed of publishing. Methods and process involved in this project for instance using bending, welding, drilling, and cutting process. This project is mainly about generating a new concept of Can Crusher that would make easier to bring anywhere and easier to crush the tins. It also can be placed beside the trash at school or any public places so that people can use it. This will reduce the space on the trash and can put a lot of aluminum tins